2019
DOI: 10.1002/ags3.12294
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of systemic inflammatory markers in esophageal cancer: Systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractAim: Impact of several immune-inflammatory markers on long-term outcome has been reported in various malignancies. The aim of the present study was to evaluate through a meta-analysis the oncological outcome of immune-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 44 publications
(78 reference statements)
0
27
1
Order By: Relevance
“…On the other hand, several other studies did not report a prognostic value for PLR (9-11). Our previous systematic meta-analysis also showed that an absence of association between PLR and OS, though NLR and CAR was significantly associated with prognosis (22). In the present study, PLR was associated with the prognosis in patients without antiplatelet or anticoagulant therapies; in patients with these therapies; however, PLR was not related to prognosis.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…On the other hand, several other studies did not report a prognostic value for PLR (9-11). Our previous systematic meta-analysis also showed that an absence of association between PLR and OS, though NLR and CAR was significantly associated with prognosis (22). In the present study, PLR was associated with the prognosis in patients without antiplatelet or anticoagulant therapies; in patients with these therapies; however, PLR was not related to prognosis.…”
Section: Discussioncontrasting
confidence: 45%
“…In the present study, we investigated the impact of antiplatelet and anticoagulant therapies on the prognostic value of platelet-related markers in patients who underwent 11 (15) 11 (10) 11 (16) 11 (10) 15 157 1016 176 715 ( 2917 2325 2622 (27) 35 2912 (22) N2 34 (19) 12 1722 2112 (17) 22 (21) 22 2112 1622 2312 1523 (19) 11 (20) N3 23 (13) 8 (11) 15 148 (12) 15 (14) 12 1211 (16) 11 (12) 12 1511 912 (22) TNM stage Ⅰ 15 145 (8) 14 (12) 12 127 108 811 (14) 7 612 (22) Tumor location Upper curative esophageal resection for ESCC. We found that although PLR was not associated with OS in the overall cohort, PLR was significantly associated with OS in patients who had not been administered antiplatelet and/or anticoagulant medications.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-related inflammation has been dubbed the 7th hallmark of cancer [4], and the systemic inflammatory response (SIR) is measured using cellular (whole white cell counts, neutrophils, lymphocytes, and platelets), and humoral (C-reactive protein (CRP) and albumin) components. Derivative biomarkers neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), neutrophil-platelet score (NPS), and the modified Glasgow Prognostic Score (mGPS), have also been reported to be associated with poor survival [5][6][7]. If SIR is to become a therapeutic target then a single, sensitive, specific, and reproducible marker is essential, but so far, although multivariable regression models have incorporated common clinic-pathological factors, no study has scrutinized the relative prognostic significance of SIR derived biomarkers in EC.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocyte, especially cytotoxic T lymphocyte, is critical in mediating cellular immunity against neoplastic cells and causing further progression and metastasis 43 45 . Clinically, the systemic inflammatory immune dynamics, presented as NLR, has been introduced to predict poor survival outcomes in esophageal cancer 23 , 25 . It represented the ratio of circulating neutrophils to lymphocytes and was supposed to correlate with the interaction between inflammation and immunity in the patient.…”
Section: Discussionmentioning
confidence: 99%